1995
DOI: 10.1007/bf01972528
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a tryptophan decarboxylase cDNA inCatharanthus roseus crown gall calluses results in increased tryptamine levels but not in increased terpenoid indole alkaloid production

Abstract: The enzyme tryptophan decarboxylase (TDC) (EC 4.1.1.28) catalyses a key step in the biosynthesis of terpenoid indole alkaloids in C. roseus by converting tryptophan into tryptamine. Hardly any tdc mRNA could be detected in hormone-independent callus and cell suspension cultures transformed by the oncogenic T-DNA of Agrobacterium tumefaciens. Supply of tryptamine may therefore represent a limiting factor in the biosynthesis of alkaloids by such cultures. To investigate this possibility, chimaeric gene construct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(29 citation statements)
references
References 42 publications
3
25
0
1
Order By: Relevance
“…Overexpression of CrWRKY1 results in an up to 3-fold increase of serpentine in C. roseus hairy roots (Fig. 8); however, overexpression of TDC does not result in similar levels of serpentine production (Goddijn et al, 1995;Hughes et al, 2004). Therefore, up-regulation of TDC alone is evidently not sufficient to explain the large increase of serpentine induced by CrWRKY1.…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulamentioning
confidence: 97%
See 1 more Smart Citation
“…Overexpression of CrWRKY1 results in an up to 3-fold increase of serpentine in C. roseus hairy roots (Fig. 8); however, overexpression of TDC does not result in similar levels of serpentine production (Goddijn et al, 1995;Hughes et al, 2004). Therefore, up-regulation of TDC alone is evidently not sufficient to explain the large increase of serpentine induced by CrWRKY1.…”
Section: Overexpression or Repression Of Crwrky1 Affects The Accumulamentioning
confidence: 97%
“…Attempts to increase TIA production by ectopic expression of genes encoding several rate-limiting enzymes have met with less than satisfactory results. For instance, despite the observation that overexpression of the Tryptophan Decarboxylase (TDC) gene has led to a moderate increase of alkaloid accumulation (Hong et al, 2006), it is generally believed that TDC activity does not correlate positively with TIA production (Goddijn et al, 1995;El-Sayed and Verpoorte, 2007). A more promising approach is the ectopic expression of transcription factors (TFs) that regulate the TIA pathway in order to enhance alkaloid production (Memelink and Gantet, 2007).…”
mentioning
confidence: 99%
“…The early availability of clones for STR and TDC led to a few metabolic engineering studies. Constitutive expression of STR in cell cultures showed a surprising positive correlation to alkaloid levels , but TDC expression resulted in elevated tryptamine levels only in transgenic cell cultures and crown gall calluses (Goddijn et al, 1995). Although elevated levels of TDC did not result in improved TIA accumulation, an antisense clone showed that TIAs were absent when TDC activity was ablated (Goddijn et al, 1995).…”
Section: Indole Alkaloidsmentioning
confidence: 93%
“…Hairy root cultures can be produced using Agrobacterium (Brillanceau et. al., 1989;Goddijn et al, 1995) and transgenic cell lines of C. roseus (van der Fits and Memelink, 1997;Hilliou et al, 1999). Although transgenic plants of C. roseus (via Agrobacterium) have been reported, no evidence of genetic transformation at the molecular level is available (Zarate et al, 1999).…”
Section: Abstract: Apocynaceae Catharanthus Roseus Indole Alkakoidsmentioning
confidence: 97%